HUBUNGAN UMUR DAN PARITAS IBU BERSALIN DENGAN KEJADIAN PREEKLAMPSIA DI RSUD BANYUMAS TAHUN 2011 - Wilis Sukmaningtyas; Gita Afriyani R (Universitas Harapan Bangsa Purwokerto, 2011)
Background :In Indonesia,maternal mortalityis stillhigh enoughin2009that226/100.000live births. Causes of maternal deathisonethat is about24% of preeclampsia. Maternalageandparitymayincrease the risk ofpreeclampsia. HospitaldatafromBanyumasfoundthat171 casesof preeclampsiacasesin 2011. Objectives : Todetermine the relationshipof age andmaternalparitywith the incidence ofpreeclampsiainBanyumasHospitalin 2011.Methods : This study wasa correlationstudywithretrospectiveapproach.Samplingtechniqueused is theTotalSampling, which isallrecordedinmaternalmedicalrecordsBanyumasHospitalin 2011as many as1801maternalpreeclampsiaornotgoodwithpreeclampsia.Results : The incidence ofpreeclampsiain womenbirthing inhospitalsBanyumasin2011was171 people(9.5%) from1801deliveries. Incidence ofpreeclampsiabyagemostlyoccursat age20-35 yearsas many as135 people(78.9%). Incidenceofpreeclampsiais based onparitylargelyoccurred inmultiparouswomenas many as81people(47.4%). The results ofchi square testfoundno associationbetweenmaternalagewiththe incidence ofpreeclampsiainBanyumasHospitalin 2011withcount=0.425x2<x2tables=5.991andpvalue =0.808>Î±=0.05. There is arelationshipbetweenmaternalparitywith the incidenceofpreeclampsiainBanyumasHospitalin 2011with12.623count =x>x2tables=5.991andpvalue =0.002<Î± =0.05.Conclusion : There was no associationbetweenmaternalagewith the incidenceofpreeclampsiainBanyumasHospitalin 2011. There is arelationshipbetweenmaternalparitywith the incidenceofpreeclampsiainBanyumasHospitalin 2011. Key words : Age, parity, preeclampsia